KEDUDUKAN DAN FUNGSI DPD DALAM KERANGKA KELEMBAGAAN LEGISLATIF INDONESIA - Dinoroy Marganda Aritonang (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
The constitutional reform beginning from 1999 has brought a lot of changes in Indonesia encompassing the constitutional system and practices of the constitution. One of the important changes is the emergence of the house of regional representatives as a partner for the first house, House of Representatives in Indonesian constitutional system. Originally, this new structure is believed as the best application of an insight to put local matters closer to national policy arena andalso become a more effective way for local governments to see the point of national vision and realize it in a local level wrapped in a strong bicameral system. Does it seem right to assume it so? Or probably, the legislative structure is still unicameral system or even, it seems as a tricameral otherwise.